REPRESENTASI MULTIKULTURALISME AUSTRALIA DALAM PUISI WOGS KARYA ANIA WALWICZ - Anwar, Desvalini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This paper discusses how far the poem ‘Wogs’ shows the representation of multiculturalism in Australia. The analysis of the poem shows that the establishment of The Australia Multicultural Policy that was planned to create harmony among the Australia plural society, on the other hand,  has caused some tensions particularly between the majority of Anglo-Celtic Australians (referred as AKA in this analysis) and the migrants of non-Anglo-Celtic descendants in Australia (referred as n-AK). The majority class represents  the non-Anglo-Celtic migrants in their country as a threat towards their life-- a threat towards the purity of Anglo-Celtic’s blood, a threat in the job fields, a threat that can lower the Australian high living standard even as a threat that is ambitious to invade the nation. However, at the same time, the poem itself also tries to construct this representation made by the Anglo-Celtic by showing alternative representations, for example: the Anglo-Celtic Australians as lazy citizens, the Anglo-Celtic Australians that are racists and the Anglo-Celtic Australians as the invader of Australia. Thus, by constructing meanings in the poem, we can see that the realities represented by the representative is not real, or not the same as those made by the represented.